2020
DOI: 10.1021/acs.chemmater.9b04925
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evaluation of the BiI3, BiOI, and Ag3BiI6 Layered Photoabsorbers

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 58 publications
6
68
0
Order By: Relevance
“…e) Energy levels of the electrode materials, electron-transport materials (ETLs), PIMs, and hole-transport materials (HTLs) used in the PIM devices. [26,51,60,62,80] der Waals interactions; [59,76] and AgBiI 4 , a representative of the rudorffite family with a general formula Ag a Bi b I x (x = a + 3b), which features a three-dimensional lattice of edge-sharing [BiI 6 ] 3or [AgI 6 ] 5octahedra. [77,78] We deposited the representative PIMs via solution-based methods (in the case of Cs 3 Sb 2 I 9 , Rb 3 Sb 2 I 9 , and AgBiI 4 ) or thermal chemical vapor deposition (in the case of BiOI) (details in the Experimental Section and Note S2, Supporting Information).…”
Section: Defect-level Characterization Of Representative Pimsmentioning
confidence: 99%
“…e) Energy levels of the electrode materials, electron-transport materials (ETLs), PIMs, and hole-transport materials (HTLs) used in the PIM devices. [26,51,60,62,80] der Waals interactions; [59,76] and AgBiI 4 , a representative of the rudorffite family with a general formula Ag a Bi b I x (x = a + 3b), which features a three-dimensional lattice of edge-sharing [BiI 6 ] 3or [AgI 6 ] 5octahedra. [77,78] We deposited the representative PIMs via solution-based methods (in the case of Cs 3 Sb 2 I 9 , Rb 3 Sb 2 I 9 , and AgBiI 4 ) or thermal chemical vapor deposition (in the case of BiOI) (details in the Experimental Section and Note S2, Supporting Information).…”
Section: Defect-level Characterization Of Representative Pimsmentioning
confidence: 99%
“…AgBiI 4 was found to exist in either the Fd true3¯ m or R true3¯ m structure, [ 314 ] whereas compounds with x / y > 1 (e.g., Ag 3 BiI 6 and Ag 2 BiI 5 ) favor the R true3¯ m phase and compounds with x / y < 1 (e.g., AgBi 2 I 7 ) favor the Fd true3¯ m phase. [ 284,310 ] The bandgaps for these materials were reported to be in the 1.63–1.90 eV range. [ 284,310,311,314–316 ] In particular, the Ag‐rich compound Ag 3 BiI 6 has a bandgap close to the optimum for indoor light harvesting (1.83–1.89 eV), [ 310 ] along with high absorption coefficients of ≈10 5 cm −1 near the band‐edge.…”
Section: Potential Of Emerging Nontoxic Materials For Indoor Photovoltaicsmentioning
confidence: 99%
“…reported a visual comparison of BiOI and Ag 3 BiI 6 , with Ag 3 BiI 6 changing in color within a week while BiOI exhibited no visual change after several months of storage in ambient conditions. [ 310 ] Sansom et al. also reported that AgBiI 4 decomposed partially to AgI after 144 min of exposure to AM 1.5G radiation in air.…”
Section: Potential Of Emerging Nontoxic Materials For Indoor Photovoltaicsmentioning
confidence: 99%
“…Layered bismuth oxyhalides (BiOX) are among many novel promising two-dimensional materials that have applications in the fields of photocatalysis and photovoltaics. [1][2][3][4][5][6][7] BiOX belongs to semiconductors of the ternary (V-VI-VII) class with a tetragonal-matlockite structure in which a layer of [Bi 2 O 2 ] 2+ is sandwiched between layers of halogen atoms with strong electrovalent bonds. [1][2][3][4][5][6][7] This unique arrangement leads to an asymmetric charge distribution between [Bi 2 O 2 ] 2+ sheets and halogen sheets; as a result, an internal static electric field is produced perpendicular to the direction of the halogen atoms along the [001] facet of BiOX.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] BiOX belongs to semiconductors of the ternary (V-VI-VII) class with a tetragonal-matlockite structure in which a layer of [Bi 2 O 2 ] 2+ is sandwiched between layers of halogen atoms with strong electrovalent bonds. [1][2][3][4][5][6][7] This unique arrangement leads to an asymmetric charge distribution between [Bi 2 O 2 ] 2+ sheets and halogen sheets; as a result, an internal static electric field is produced perpendicular to the direction of the halogen atoms along the [001] facet of BiOX. [1][2][3][4][5][6][7] This internal electric field plays a prominent role in chargecarrier separation in BiOX photocatalysts, and is responsible also for their enhanced photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%